2010
DOI: 10.1074/jbc.m110.109488
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hepatocyte Hemojuvelin in the Regulation of Bone Morphogenic Protein-6 and Hepcidin Expression in Vivo

Abstract: Both hemojuvelin (HJV) and bone morphogenic protein-6 (BMP6) are essential for hepcidin expression. Hepcidin is the key peptide hormone in iron homeostasis, and is secreted predominantly by hepatocytes. HJV expression is detected in hepatocytes, as well as in skeletal and heart muscle. HJV binds BMP6 and increases hepcidin expression presumably by acting as a BMP co-receptor. We characterized the role of hepatocyte HJV in the regulation of BMP6 and hepcidin expression. In HJV-null (Hjv Iron is an indispensable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
79
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 31 publications
11
79
1
4
Order By: Relevance
“…Similar data were recently obtained with hemojuvelin-deficient mice on a 129/SvEvTac background. 15 Hemojuvelin …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar data were recently obtained with hemojuvelin-deficient mice on a 129/SvEvTac background. 15 Hemojuvelin …”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] Interestingly, whereas Hjv-deficient mice have Bmp6 mRNA levels 4 times higher than wild-type mice in their liver, no significant difference in Bmp6 mRNA expression was found in their small intestine. 15 Immunodetection was performed with two Santa Cruz anti-BMP6 antibodies, S-20 as in Arndt et al 11 and N-19 as in Kautz et al 10 A centrilobular pattern of Bmp6 staining was observed in the liver of iron overloaded mice. Noticeably, the centrilobular Bmp6 staining in these mice does not coincide with the periportal location of iron visualized by Perls' coloration, which excludes iron interference with immunodetection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At the molecular level, Hamp expression is controlled by the activation of the SMAD1,5,8/SMAD4 complex, which in turn is triggered by the association between the BMP6 ligand, whose expression is proportional to intracellular hepatic iron concentrations, and the BMP-receptor complex (10)(11)(12). Hemojuvelin (HJV) acts as a coreceptor and is required to fully activate the SMAD pathway (10,(13)(14)(15). In contrast, TMPRSS6 or Matriptase-2, a transmembrane serine protease, cleaves HJV, reducing the phosphorylation of the SMAD complex and attenuating HAMP expression (16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…HJV is highly expressed in the liver, heart and skeletal muscle. In the liver, only hepatocytes express HJV but no other cells [60,61]. HJV plays an important role in hepcidin expression [62].…”
Section: Hemojuvelinmentioning
confidence: 99%